Latin-American Registry of Cardiovascular Disease and COVID-19: Rationale and Design of the CARDIO COVID 19-20 Registry. Issue 1 (12th February 2021) - Gómez-Mesa, Juan Esteban; Galindo-Coral, Stephania; Montes, Maria Claudia; Alarco, Walter; Barisani, Jose Luis; Magaña, Antonio; Perna, Eduardo R.; Romero, Alexander; Speranza, Mario; Mendoza, Iván; Wyss, Fernando
Background: Infection caused by SARS-CoV-2 (severe acute respiratory syndrome coronavirus 2) exhibits a strong infectivity but less virulence compared to severe acute respiratory syndrome (SARS) and the Middle East respiratory syndrome (MERS). In terms of cardiovascular morbidity, susceptible population include elderly and patients with certain cardiovascular conditions. This infection has been associated with cardiac injury, cardiovascular complications and higher mortality. Objectives: The main objective of the CARDIO COVID 19-20 Registry is to determine the presence of cardiovascular comorbidities and cardiovascular complications in COVID-19 infected patients that required in-hospital treatment in different Latin American institutions. Methods: The CARDIO COVID 19-20 Registry is an observational, multicenter, ambispective, and hospital-based registry of patients with confirmed COVID-19 infection who required in-hospital treatment in Latin America. Enrollment of patients started on May 01, 2020 and was initially planned to last three months; based on the progression of pandemic in Latin America, enrollment was extended until December 2020, and could be extended once again based on the pandemic course in our continent at that moment. Conclusions: The CARDIO COVID 19-20 Registry will characterize the in-hospital population diagnosed with COVID-19 in Latin America in order to identify risk factors for worsening of cardiovascular comorbidities or for the appearance of cardiovascular complications during hospitalization and during the 30-day follow up period.